Gambaran Tingkat Kecemasan Warga tentang Bencana Tanah Longsor Akibat Penambangan Liar di Desa Paseban Klaten - Herawati, Nora; Susilowati, Tri (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2025)
Landslides are natural disasters that cause significant harm to communities, commonly triggered by extreme geomorphological conditions and tropical climates. In Indonesia, 809 landslide incidents have been recorded. These disasters not only disrupt daily life but also impact mental health. While many individuals exhibit normal psychological responses, others may experience disorders such as PTSD, psychosis, depression, and severe anxiety. Objective: To identify the characteristics of respondents and describe the anxiety levels of residents regarding landslides caused by illegal mining in Paseban Village, Klaten. Method: This study employed a descriptive quantitative design using cluster random sampling. The total population was 5,393, with 98 respondents selected as the sample. Results: Most respondents were adults aged 20–44 years (40.8%) and female (58.2%). The majority had an elementary school education (46.9%). The residents' anxiety level regarding landslides caused by illegal mining was predominantly in the mild anxiety category (43.9%). Conclusion: The majority of residents in Paseban Village, Klaten, experienced mild anxiety related to landslide disasters caused by illegal mining.